Interview: Gender Imbalance in the Law - Grice, Christine (Victoria University of Wellington Law Review, 2016)
Following the release of the Auckland Women Lawyers' Association funded research Women's career progression in Auckland law firms: Views from the top, views from below, the Executive Director and past-President of the New Zealand Law Society, Christine Grice, did some research into the situation of women QCs. She explored the issues facing senior women lawyers in an interview with Kathryn Ryan on "Nine to Noon" on 10 March 2014. On 6 June 2014, the 14 new QCs announced, included four women, with the Attorney-General saying: "I am aware there are very talented women in the profession who remain reticent about putting their names forward and I hope to see increasing numbers represented in the future."